2011
DOI: 10.1007/s11284-011-0865-9
|View full text |Cite
|
Sign up to set email alerts
|

Persistent soil seed banks in old‐growth Hyrcanian Box tree (Buxus hyrcana) stands in northern Iran

Abstract: Little is known about the soil seed bank and the influence of plant communities on the interaction between the seed bank and aboveground vegetation in the Hyrcanian temperate deciduous forest. We surveyed species composition and diversity of the persistent soil seed bank and the aboveground vegetation in six community types in old-growth Hyrcanian Box tree (Buxus hyrcana) stands in northern Iran. Fifty-two species with an average of 3,808 seeds/spores m À2 germinated; forbs accounted for 64% of the seed bank f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In herbaceous layer, Whittaker nested plot sampling and minimal area method were used to survey the percentage cover of each herbaceous species according to the Braun-Blanquet scale (Mueller-Dombois, Ellenberg, 1974). Then, Flora Iranica (Rechinger 1989), Flora of Turkey (Davis 1970), Flora of Iran and the Colourful Flora of Iran (Ghahreman 1978) were used to identify dried species (Asadi et al 2011). As for soil sampling in each plot, four soil samples were randomly taken from 0-30 cm depth of mineral soil, and after mixing one compositesoil sample was prepared (approximately 500 g) (Salehi et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…In herbaceous layer, Whittaker nested plot sampling and minimal area method were used to survey the percentage cover of each herbaceous species according to the Braun-Blanquet scale (Mueller-Dombois, Ellenberg, 1974). Then, Flora Iranica (Rechinger 1989), Flora of Turkey (Davis 1970), Flora of Iran and the Colourful Flora of Iran (Ghahreman 1978) were used to identify dried species (Asadi et al 2011). As for soil sampling in each plot, four soil samples were randomly taken from 0-30 cm depth of mineral soil, and after mixing one compositesoil sample was prepared (approximately 500 g) (Salehi et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…2), and Pielou's evenness index (E; Eq. 3) (Asadi et al, 2012) were used to evaluate the species diversity of soil seed banks and aboveground vegetation for each quadrat.…”
Section: Plant Species Diversity Indicesmentioning
confidence: 99%
“…Viable seeds of those species may not accumulate in the soil, because of a greater risk of mortality -by recalcitrance (oak acorns) as well as by predation by animals (Lambers et al, 2005), or because virtually all viable seeds germinated in the spring (Esmailzadeh et al, 2011). A previous study in the Hyrcanian forest also showed that all the species that were either recorded only in the above-ground vegetation and absent from seed bank, or abundant in the vegetation but rare in the seed bank were tress and long-lived perennials (Asadi et al, 2012). Surprisingly, Trifolium angustifolium was never found in the above-ground vegetation of the study area but found in the seed bank of all the three habitats.…”
Section: The Relationship Between the Soil Seed Bank And Above-groundmentioning
confidence: 97%